1990
DOI: 10.1093/rheumatology/29.6.465
|View full text |Cite
|
Sign up to set email alerts
|

Methylsulphasalazine in Rheumatoid Arthritis

Abstract: Methylsulphasalazine, which differs from sulphasalazine by the addition of one methyl group, may provide the benefits of the parent drug with fewer side-effects in rheumatoid arthritis (RA). We describe the outcome of its use in RA. Of 21 patients entered into the study, 10 successfully completed 6 months of therapy; five developed adverse effects, four withdrew for reasons unrelated to drug treatment and two stopped because of inefficacy. No serious adverse effects were reported. A statistically significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Some in vitro and in vivo animal studies havc suggested that SSZ has inherent immunologic activities that SP and ASA do not possess (22)(23)(24). The significance of thcse observations is difficult to assess, but a study of methylsulfasalazinc (MSSZ) in RA has provided indircct evidence supporting thc theory that SSZ may havc antirheumatic properties of its own (25). MSSZ is more lipid soluble than SSZ, thus enabling the parent molecule to be absorbed largely unchangcd in the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Some in vitro and in vivo animal studies havc suggested that SSZ has inherent immunologic activities that SP and ASA do not possess (22)(23)(24). The significance of thcse observations is difficult to assess, but a study of methylsulfasalazinc (MSSZ) in RA has provided indircct evidence supporting thc theory that SSZ may havc antirheumatic properties of its own (25). MSSZ is more lipid soluble than SSZ, thus enabling the parent molecule to be absorbed largely unchangcd in the small intestine.…”
Section: Discussionmentioning
confidence: 99%